A comparative analysis of the circular economy performances for European Union countries. Issue 7 (3rd October 2022) - Candan, Gökçe; Cengiz Toklu, Merve
ABSTRACT: Circular economy (CE), which has emerged with the integration of environmental science and sustainable development, has a significant contribution to human development and is a constantly developing concept that can be measured at the country, region, city, or enterprise level. Evaluating the CE performances of the European Union (EU) member countries at specific periods is crucial for monitoring their development. This study bridges the gap in the literature in terms of the method, dataset, and comparative analysis used while measuring the CE performances, and this is one of the first studies to look at the importance weights of CE criteria. In this study, a novel approach is proposed to evaluate the CE performances of EU member countries. The evaluation criteria are based on the European Commission CE monitoring framework in the proposed approach. The importance weights of criteria are determined using the fuzzy Simple Multi-Attribute Rating Technique (SMART) approach. The EU member countries are ranked according to their CE performances with the Combinative Distance-Based Assessment (CODAS) method considering the weights of the evaluation criteria. The proposed evaluation approach is applied by taking 2014, 2016, and 2018 years data into account. As a result of the application, according to the CE efficiency, the top five countries are the Netherlands, Luxembourg, Belgium, France, and Germany. The study's findings can assist researchers and policymakers in gaining a better understanding of countries' CE performance levels.